Academy of Nutrition and Dietetics/American Society for Parenteral and Enteral Nutrition Consensus Malnutrition Characteristics: Usability and Association With Outcomes. (10th May 2019) - Mogensen, Kris M.; Malone, Ainsley; Becker, Patricia; Cutrell, Stephanie; Frank, Laura; Gonzales, Kelly; Hudson, Lauren; Miller, Sarah; Guenter, Peggi; ,
Abstract: Malnutrition has been documented in approximately one‐third of patients in developed countries on hospital admission and is associated with negative clinical outcomes. The need to identify and intervene in at‐risk patients is critical to minimize these negative outcomes. A consensus approach for diagnosing and documenting malnutrition in hospitalized adult and pediatric patients was published jointly by the Academy of Nutrition and Dietetics (Academy) and the American Society for Parenteral and Enteral Nutrition (ASPEN) in 2012 and 2014, respectively. The purpose of this paper is to review the available literature on the usability, feasibility, validity, and reliability of both the adult and pediatric consensus malnutrition diagnostic approaches, as well as to evaluate their use in studying clinical outcomes. In adults, abstracts and published studies have shown the diagnostic tool is a usable, feasible, and reliable method for the identification of severe and non‐severe or moderate malnutrition. In pediatrics, only 1 published study to date used the pediatric malnutrition indicators, indicating the need to demonstrate that the tool is feasible, valid, and reliable. Both the adult and pediatric tools have shown significant correlation with negative clinical outcomes in malnourished patients, including increased mortality, increased hospital length of stay (adults), increased complications (pediatrics), and increased hospital readmissions. Further large‐scale studies are needed to evaluate the feasibility, usability, validity, and reliability of both the adult and pediatric malnutrition diagnostic approaches.